PENGELOLAAN PERSIAPAN AKREDITASI SEKOLAH - Emilia Nur Chasanah Sholihin; Ibrahim Bafadal; Asep Sunandar (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2018)
Abstract: The purposes of this research to describe: (1) the process of establishing school accreditation teams, (2) completing accreditation instruments and physical evidence, (3) inhibiting and supporting factors in preparation of school accreditation, (4) quality control of process completing accreditation instrument and physical evidence, (5) follow-up preparation of school accreditation, and (6) successful strategies in school accreditation. This research uses a qualitative approach, with a case study research design. Research location at SDN Ketawanggede Malang. Data collection techniques with interviews, observation, and documentation. The results of this research (1) the process of establishing the team through the appointment of the team leader by the principal, drafting SK, meeting and making SK team, (2) completing the accreditation instrument and physical evidence through attending socialization, checklist of accreditation instruments, preparation of accreditation data and fulfillment of physical evidence , (3) inhibiting factors such as time constraints, the existence of teacher mutation, pension and death, the document is irregular and printer is inadequate while the supporting factors are principal assistance and motivation, inter-team collaboration, and assistance of school stakeholders (4) control through checks and evaluation meetings, (5) follow-up preparations by familiarizing the completeness of school equipment, establishing school programs, and undertaking quality assurance through the SPMI team, and (6) success strategies in school accreditation there are strategies to get score A values and strategies for rapid done.Keyword: management, preparation, school accreditationAbstrak: Penelitian ini bertujuan untuk mendeskripsikan: (1) proses pembentukan tim akreditasi sekolah, (2) pelaksanaan pengisian instrumen akreditasi dan bukti fisik, (3) faktor penghambat dan pendukung dalam persiapan akreditasi sekolah, (4) quality control dari proses pengisian instrumen akreditasi dan bukti fisik, (5) tindak lanjut persiapan akreditasi sekolah, dan (6) strategi keberhasilan dalam akreditasi sekolah. Penelitian ini menggunakan pendekatan kualitatif, dengan rancangan penelitian studi kasus. Lokasi penelitian di SDN Ketawanggede Malang. Teknik pengumpulan data dengan wawancara, observasi, dan dokumentasi. Hasil penelitian ini (1) proses pembentukan tim melalui penunjukan ketua tim oleh kepala sekolah, membuat draft SK, rapat dan membuat SK tim, (2) pelaksanaan pengisian instrumen akreditasi dan bukti fisik melalui menghadiri sosialisasi, melakukan checklist instrumen akreditasi, persiapan data akreditasi dan  pemenuhan bukti fisik, (3) faktor penghambat yaitu keterbatasan waktu, adanya guru mutasi, pensiun dan meninggal dunia, dokumen letaknya tidak beraturan dan printer kurang memadai sedangkan faktor pendukung yaitu bantuan dan motivasi kepala sekolah, kerja sama antar tim, dan bantuan stakeholders sekolah (4) quality control melalui pengecekan dan rapat evaluasi, (5) tindak lanjut persiapan dengan membiasakan kelengkapan perangkat sekolah, membuat program sekolah, dan melakukan penjaminan mutu melalui tim SPMI, dan (6) strategi keberhasilan dalam akreditasi sekolah terdapat strategi untuk mendapatkan nilai A dan strategi supaya cepat selesai.Kata Kunci: pengelolaan, persiapan, akreditasi sekolah